One-Stage Femtolaser-Assisted Lamellar Keratoplasty and Foreign Body Removal. Issue 2 (February 2015) - Taneja, Mukesh; Rathi, Varsha M.; Bagga, Bhupesh
ABSTRACT Purpose To report the use of femtosecond laser platform to remove a glass foreign body (FB) and remove scar by performing sutureless lamellar keratoplasty. Case Report A 34-year-old man presented with a posttraumatic anterior stromal scar and retained corneal glass FB after injury to his left eye, sustained in a prior vehicular accident. Right eye examination was essentially normal. Best-corrected visual acuity of the left eye was 20/320. He underwent femtosecond laser–assisted sutureless anterior lamellar keratoplasty using the 500-kHz femtosecond laser machine. The host bed and donor lenticule diameters were 7.9 and 7.8 mm and the thickness of the lenticule was 125 and 150 μm, respectively. The recipient lenticule was obtained by placing the lamellar incision that encompassed the FB. When the recipient lenticule was lifted, partially embedded FB present in the stroma was removed after dislodging it with a 26-gauge needle. The femtosecond-dissected donor button was placed onto the stromal bed with a snug fit. No sutures were taken. Postoperatively, best-corrected visual acuity improved to 20/50 at 1 month and 20/30 at 7 months of follow-up. Conclusions Femtosecond laser–assisted sutureless anterior lamellar keratoplasty is a promising modality for lamellar keratoplasty, and as the depth of the incision can be obtained with precision, impacted stromal FBs can be removed in a single procedure along with scars.